Impact of Income and Corporate Taxes on Economic Development in Egypt - Abo-Ahmed, Khaled (AUC Knowledge Fountain, 2021)
The purpose of this study is to examine how do corporate and income taxes impact economic development in Egypt. This study uses the analytical quantitative method, and the approach of this study is based on using annual time series data for the period 1980 to 2018 to estimate two models by using Autoregressive distributed lag (ARDL) model. First estimation is between direct taxes (corporate and income taxes) and Growth domestic product (GDP) growth as dependent variable, and the second one by using human development index (HDI) instead of GDP growth. The second objective is to investigate the difference, if any, with the result obtained by using HDI and GDP in estimating the impact of the corporate and income taxes on the economic development of Egypt. Findings show a positively and significantly relationship between direct tax (Income and Corporate taxes) and economic growth in Egypt, and negative relationship between direct tax (Income and Corporate taxes) and economic development. The researcher, therefore, conclude that the implication of tax revenue is not making as much impact on economic development as on gross domestic product of Egypt. Thus, the Egyptian government should work more on encouraging its people to create trust in it through tax transparency, ensuring high fulfillment of the promises made to the public. This study provides a useful insight for the policy makers, stakeholders and government into the importance of tax revenue for economic development as a result; revenue derived from tax should be wisely used to encourage people to continue to pay tax.